PENGARUH PENGGUNAAN MEDIA AUGMENTED REALITY TERHADAP AKTIVITAS BELAJAR DAN KEMAMPUAN BERPIKIR SPASIAL SISWA MATERI KARAKTERISTIK LAPISAN-LAPISAN BUMI DI SMA N 1 TALAMAU - Nurul Halimah; Ahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of using Augmented Reality media on learning activities and spatial thinking skills of students by using Augmented Reality media in learning geography at SMA N 1 Talamau, West Pasaman Regency. The method in this study is a quantitative method, the research design used is a quasi experimental design with a research design of nonequivalent control group design. Data collection is done by observation, tests and documentation. Data analysis with percentages, t-test (Independent sample t-test), and N-Gain. The results showed that the percentage of learning activities in the experimental class was 83.25%, including a very effective category. While the control class of 61.73% is included in the less effective category. Then the results of data analysis of students' spatial thinking abilities in the independent sample t-test show the results of two sided p (sig2-tailed) <0.001 smaller than 0.05 indicating that there is a significant difference between the two sample groups. Strengthened by the results of the N-Gain% of students' spatial thinking ability of the experimental class of 61.2477% including the moderately effective category and N-Gain% in the control class of 23.2252% including the ineffective category.